Electrochemical DFT and MD Simulation Study of Substituted Imidazoles as novel Corrosion Inhibitors for mild Steel - Dohare,Parul (2019)
Three substituted imidazoles 2-(3-methoxyphenyl)-4,5-diphenyl-1H-imidazole (IM-1), 2,4,5-triphenyl-1H-imidazole (IM-2), and 2-(3-nitrophenyl)-4,5-diphenyl-1H-imidazole (IM-3) were synthesized, and their inhibiting action was tested using mass loss, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) methods. The results show that methoxy substituted imidazole performed better as a corrosion inhibitor than NO2 substituted imidazole. These findings were corroborated by density functional theory (DFT) and molecular dynamics (MD) simulations methods. IM-1 was found to exhibit maximum IE of 97.5%, at 100 mgL-1, among the studied IMs. PDP study revealed that all the three IMs inhibitors predominantly acted as cathodic inhibitors, and the adsorption study showed that they followed Langmuir adsorption isotherm. The formation of an inhibitor film on the MS surface was confirmed by scanning electron microscopy (SEM) and atomic force microscopy (AFM). MD study revealed that binding energy and interaction energy of the inhibitors molecules on the MS surface followed the order IM-1> IM-2> IM-3. All the three IMs molecules adsorbed onto the mild steel surface by flat orientation. DFT and MD study results corroborated the experimental results.